Quality class of Betung Bamboo fiber (Dendrocalamus Asper) from West Sumatra and its Potential as a Raw Material for Paper - Mutiar, Sri; Anggia, Malse; Putra, Yogi Riyanda; Aini, Nurul (Journal of Fibers and Polymer Composites, 2025)
Betung bamboo is one of the Non-Timber Forest Products referring to the Minister of Forestry Regulation P.35 / MENNUT-II / 2007.  In Indonesia, betung bamboo (Dendrocalamus asper) is included in the type of large bamboo which has a very wide potential for pulp and paper raw materials. Identification information of betung bamboo from Agam district, West Sumatra is important to know. Bamboo characteristics include the characteristics and dimensions of bamboo fibers based on bamboo stem sections. The purpose of this study was to determine the characteristics and physical properties of betung bamboo based on bamboo stem section. The research method used in this study uses observation and experimental research methods. The results showed that the water content of betung bamboo showed that the base had a higher water content than the top. While the density, thickness and diameter of the bamboo at the base is higher than the middle and top of the bamboo.